2008
DOI: 10.1097/nmd.0b013e3181773927
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Burden and Health in Bipolar Disorder

Abstract: To identify caregivers at risk for adverse health effects associated with caregiving, the stress, coping, health and service use of 500 primary caregivers of patients with bipolar disorder were assessed at baseline, 6, and 12 months. K-means cluster analysis and ANOVA identified and characterized groups with differing baseline stress/coping profiles. Mixed effects models examined the effects of cluster, time, and covariates on health outcomes. Three groups were identified. Burdened caregivers had higher burden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 43 publications
(46 reference statements)
2
51
1
1
Order By: Relevance
“…24 They may perceive caregiving as burdensome or stressful, [25][26][27] and they report greater feelings of strain, 27 more stressful life events, 28 and greater disruption in family functioning. 27 Perlick and colleagues 25 found a high use of avoidance coping strategies by family members of persons with mental illness. Although avoidance coping may be a less-than-optimal method for coping, it is possible that this coping method may also be protective; thus, risk factors in one context may be protective in another.…”
Section: Risk/vulnerability Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 They may perceive caregiving as burdensome or stressful, [25][26][27] and they report greater feelings of strain, 27 more stressful life events, 28 and greater disruption in family functioning. 27 Perlick and colleagues 25 found a high use of avoidance coping strategies by family members of persons with mental illness. Although avoidance coping may be a less-than-optimal method for coping, it is possible that this coping method may also be protective; thus, risk factors in one context may be protective in another.…”
Section: Risk/vulnerability Factorsmentioning
confidence: 99%
“…51 In family caregivers, greater mastery has been associated with lower caregiver burden and psychological distress and a greater sense of competence in the caregiving role. 25,52 Five studies of family members of persons with mental illness have examined mastery, which may be viewed as an indicator of resilience. Murray-Swank and colleagues 22 studied 83 caregivers of persons with serious mental illness to examine whether religiosity was associated with psychosocial adjustment and caregiver burden.…”
Section: Masterymentioning
confidence: 99%
“…Coping strategies include problem solving, support seeking, and avoidance (Scazufca & Kuipers, 1996, 1999Nehra, Chakrabarti, Kulhara, & Sharma, 2005). A positive correlation has been observed between caregiver burden and use of avoidance as a coping strategy (Chadda, Singh, & Ganguly, 2007;Perlick et al, 2008). A higher perception of burden has been reported to be associated with poor outcome in persons with BAD, the relationship probably being mediated through families' affective response and patients' medication adherence (Perlick et al, 2004(Perlick et al, , 2007.…”
mentioning
confidence: 95%
“…Research done by Dore and colleagues, focuses on the influence of relatives and family members on patient's occupation, financial and residential status, marital status, child care, social and even recreational activities. (Dore & Romans, 2001) It was found that burden of the disease on family members may affect outcome of the disease (Perlick et al, 2008). Several long term and short term programs have been designed for family members of patients.…”
Section: Nonpharmacological Treatments For Bmdmentioning
confidence: 99%